Modern weapons and military equipment for issue 4-2020 - Jevtić, Miloš M. (Vojnotehnički glasnik / Military Technical Courier, 2020)
This paper describes and analyses construction details of the Corner Shot platform, in order to shape its flaws and traits.
Keywords: modern; weapons; military equipment